Pengaruh Sikap Dan Norma Subyektif Terhadap Minat Konsumen (Studi Pada Pengguna Refill Tinta Printer Dataprint Di Banjarmasin) - Sri Imelda; Rofi'i . (Jurnal Study and Management Research, 2014)
This research aims to proof empirically that attitude and subjective norm influence the interest. This concept is practically due to Data Print refill ink consumer’s in Banjarmsin city. The reasoned action model was developed by Fishbein and Ajzen in 1980. Attitude was formed through the believe of DataPrintproduk marketing mix before buying and using the product which means firstabelevery body have believe to the product before he/she buys it and then evaluate them due the process subjective norm was formed by other people references and motivation to follow other people which means some body ussually looking for information from another person beffore he/she decides to buy or use the product. The conlusion from this research are : 1). There are positive and significantly influence between attitude and subjective norms due to interest, partially and simultaneously; 2). 63,7 % is the biggest simulttaneous influence between attitude and subjective norms due to interest. Mean while 36,3% is explained by another factors and error such as earning, location and transportation; 3). This multiple linier regresian model can be used to predict the change of interest due to attitude and subjective norm changing